The Competency Gap of Hotel Management Graduates from Hotel Supervisor's Perspective - Andi Kele, Andi Tamsang; Syed Khalid Wafa, Syed Azizi Wafa (Universiti Utara Malaysia Press, 2012)
The hotel industry has gained prominence in Malaysia and with the global nature of the industry, human resource issues need to be addressed to ensure that the industry remains competitive. This quantitative research provides a comprehensive study on the competency gap of hotel management graduates from the employers perspectives. This study looks at the expectation and observation of hotel supervisors towards hotel management graduates in Kota Kinabalu, Sabah. A total of 200 questionnaires were sent out to all the star-rated hotels in Kota Kinabalu, Sabah, and 100 usable responses were received and analysed. It was found out that there is a gap in terms of work-related competencies of the Hotel Management (HM) graduates from the hotel supervisor's perspective. It is suggested that the educational institutions and other training organizations pay attention to the results of this study since it was found that the hotel supervisors felt the work-related competency provided by the institutions where the HM graduates are trained is below their expectation and as such, it needs to be improved.